2015
DOI: 10.1002/anie.201502980
|View full text |Cite
|
Sign up to set email alerts
|

Three‐Component Azidation of Styrene‐Type Double Bonds: Light‐Switchable Behavior of a Copper Photoredox Catalyst

Abstract: [Cu(dap)2]Cl effectively catalyzes azide addition from the Zhdankin reagent to styrene-type double bonds, and subsequent addition of a third component to the benzylic position. In the presence of light, a photoredox cycle is implicated with polar components such as methanol or bromide adding to a benzylic cation. In the absence of light, by contrast, double azidation takes place to give diazides. Therefore, regioselective double functionalization can be achieved in good to excellent yields, with a switch betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
108
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(114 citation statements)
references
References 78 publications
(36 reference statements)
2
108
1
Order By: Relevance
“…Greany and co-workers found that [Cu(dap) 2 ] + is able to catalyze azide addition to styrene-type double bondsw hen using ah ypervalent iodine reagent (43)a sa na zide source (Scheme 12). [35] In the dark, the lifetime of the resulting benzyl radicali ntermediate is long enought hat another azide radical can add to form bis(azide) products ( 44 b). Upon photoirradiation of [Cu(dap) 2 ] + ,oxidation to the benzylic radical cation presumably takes place, followed by subsequentt rappingw ith methanol (44 a), bromide anions, or other nucleophiles.…”
Section: Chromium IIImentioning
confidence: 99%
“…Greany and co-workers found that [Cu(dap) 2 ] + is able to catalyze azide addition to styrene-type double bondsw hen using ah ypervalent iodine reagent (43)a sa na zide source (Scheme 12). [35] In the dark, the lifetime of the resulting benzyl radicali ntermediate is long enought hat another azide radical can add to form bis(azide) products ( 44 b). Upon photoirradiation of [Cu(dap) 2 ] + ,oxidation to the benzylic radical cation presumably takes place, followed by subsequentt rappingw ith methanol (44 a), bromide anions, or other nucleophiles.…”
Section: Chromium IIImentioning
confidence: 99%
“…[1h] Therefore, searching for a general, yet selective olefin diazidation method has been an important research topic and a range of methods for certain limited types of olefins have been developed. [3] …”
mentioning
confidence: 99%
“…However, this method is incompatible with nonstyrenyl olefins. [3a] Fristad and coworkers reported a Mn III -mediated stoichiometric method only for nonfunctionalized aliphatic olefins with a large excess of NaN 3 in acetic acid at 110°C. Snider later reported a key improvement using TFA at −20°C.…”
mentioning
confidence: 99%
See 2 more Smart Citations